CDSS implementation processes in the East Malaysian government hospitals during COVID-19 pandemic - Syed Nasirin Syed Zainol Abidin; Tamrin Amboala; Soffri Yussof; Suraya Miskon; Lung, Jackel Chew Vui; Nur Faraha Mohd. Naim; Hadzariah Ismail; Abdul Kadir NAA (Elsevier, 2024)
Clinical Decision Support Systems (CDSS) have been shown to reduce medical mistakes, but their implementation can sometimes be demanding. This exploratory study aimed to pinpoint key characteristics for implementing CDSS in government hospitals in East Malaysia. Through in-depth case studies and focus group interviews, essential determinants were identified, including technical support, communication and collaboration, and user readiness for new technology. The analysis revealed these determinants as crucial for CDSS implementation. The findings and proposed framework are valuable in assisting the hospitals in establishing guidelines for implementing CDSS, particularly in the context of the COVID-19 era. By considering these insights, hospitals may leverage CDSS to reduce medical errors and enhance patient care.